2007
DOI: 10.1016/j.vaccine.2007.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunization of mice with the live vaccine strain (LVS) of Francisella tularensis protects mice against respiratory challenge with virulent type A F. tularensis

Abstract: Francisella tularensis is a gram-negative intracellular bacterium, and the causative agent of tularemia. The infection can be initiated by various routes and can manifest itself in several clinical forms with the disseminated typhoidal form initiated by inhalation being most fatal. The attenuated live vaccine strain (LVS), developed almost 50 years ago, remains the sole effective tularemia vaccine, which is still only available as an Investigational New Drug for at-risk individuals. This vaccine, when given by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
57
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 26 publications
6
57
0
Order By: Relevance
“…For histopathological examination, the lung and spleen were fixed immediately in 10% neutral buffered formalin and processed by standard paraffin embedding methods (Department of Pathology and Laboratory Medicine, University of Ottawa, Ottawa, Ontario). Sections were cut 4 m thick, stained with hematoxylin-eosin, and examined by light microscopy (19).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…For histopathological examination, the lung and spleen were fixed immediately in 10% neutral buffered formalin and processed by standard paraffin embedding methods (Department of Pathology and Laboratory Medicine, University of Ottawa, Ottawa, Ontario). Sections were cut 4 m thick, stained with hematoxylin-eosin, and examined by light microscopy (19).…”
mentioning
confidence: 99%
“…For cytokine/chemokine mRNA expression analysis, the lung and spleen were dissected, immersed immediately in RNAlater (QIAGEN, Germantown, MD), and stored at Ϫ20 o C until extraction. Relative amounts of cytokine and chemokine mRNAs in the lung and spleen over the course of infection in the two groups of mice were estimated using a real-time PCR-based method essentially as described elsewhere (13,19). Briefly, total RNA was extracted from tissues, and cDNA was prepared, amplified, and quantified using primers and probes designed with the Primer3 program available at http://frodo.wi.mit.edu/cgi-bin/primer3/primer3_www.cgi.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It was the objective of this study to provide data on differences in the susceptibility of Mus musculus (BALB/c mice), Apodemus flavicollis (yellow-necked mouse) and Microtus arvalis (common vole) to F. tularensis infection. While BALB/c mice represent the standard, as they are genetically defined experimental animals with much data available concerning their response to infection by F. tularensis Conlan et al, 2003;Green et al, 2005;KuoLee et al, 2007), yellow-necked mice and common voles have been reported to harbour F. tularensis with as high a prevalence as 3.9% during activation of tularemic foci in Central Europe (Gurycova et al, 2001;Vyrostekova et al, 2002). Though Dunaeva and Olsufyev (1958) consider these species highly susceptible to tularemia, the results of the present study demonstrate that there is a two-orders-of-magnitude difference in susceptibility to F. tularensis infection between BALB/c mice and common voles, with mice being more susceptible.…”
Section: Discussionmentioning
confidence: 99%